Consumer Trust and Intentions in Using Halal Self-Declare Certification Among Food Micro-Enterprises in Jakarta - Aldian Aldian (Tinta Emas Publisher, 2024)
This study examines consumer trust and behavioural intentions toward halal self-declare certification among food micro-enterprises in Jakarta. The self-declare certification system was introduced to simplify halal certification access for micro and small enterprises, particularly those producing low-risk food products with simple ingredients and production processes. However, its implementation raises important questions regarding consumer trust, process transparency, and business adoption. This study employed a qualitative research design using netnography, in-depth interviews, observation, and documentation. Netnographic data were collected from Indonesian-language digital platforms, while interviews were conducted with Muslim consumers and food micro-enterprise owners in Jakarta. The data were analysed thematically with the assistance of NVivo to identify major themes and patterns across data sources. The findings show that consumer awareness of halal self-declare certification remains limited. Although consumers generally recognise halal labels, many do not clearly understand the difference between conventional certification and the self-declare pathway. Consumer trust is shaped by institutional credibility, process transparency, perceived religious risk, and the visibility of certification information. From the business perspective, micro-enterprise owners view self-declare certification as beneficial because it reduces cost, accelerates certification, and improves customer confidence. However, they also face barriers related to digital literacy, documentation, and consumer scepticism. This study concludes that halal self-declare certification has strong potential to expand halal assurance among micro-enterprises, but its effectiveness depends on clearer public communication, transparent certification display, and stronger support for business owners.